Incorporating Multiple Objectives in Planning Models of Low-Resource Farmers - Flinn, J.C.; Jayasuriya, S.; Knight, C.G. (Wiley, 1980)
Linear goal programming provides a means of formally incorporating the multiple goals of a household into the analysis of farming systems. Using this approach, the set of plans which come as close as possible to achieving a set of desired goals under conditions of land and cash scarcity are derived for a Filipino tenant farmer. A challenge in making LGP models empirically operational is the accurate definition of the goals of the farm household being modelled.